2017
DOI: 10.21767/2172-0479.100120
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Detection of Mycobacterium tuberculosis (MTB) and Rifampicin Resistant Strain among Subjects Accessing Health Care at Federal Medical Centre, Yenegoa, Bayelsa State; Nigeria

Abstract: Background: An increasing global incidence of Mycobacterium Tuberculosis (MTB), and emergence of drug resistant strains of MTB, have critically promoted the urgent need to explore better effective methods that can rapidly detect MTB, and identify drug-resistant cases as recommended by World Health Organization report of 2008. Globally, multi-drug-resistant strains of MTB are increasingly becoming a huge public health issue, which has adversely affected the health care delivery of patients, especially in develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
1
7

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 10 publications
6
1
7
Order By: Relevance
“…In this study, Mycobacterium tuberculosis was prevalent in all ages, but have seriously hit the age group of 30-44 years with 26.0% and of whom 34/420 (8.1%) were rifampicin resistant. The positivity nding was in line with studies conducted in Gondar (29.8%) [14], different studies in Ethiopia [21][22][23]35], WHO reports 2017 [2] and Agaro Teaching Health Center in southwestern Ethiopia [36].However, contrary ndings with several studies in a different part of Nigeria and Zambia [18,24,33] which had lower prevalence, but higher than a study conducted in eastern Uttar Pradesh (40%) [19].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In this study, Mycobacterium tuberculosis was prevalent in all ages, but have seriously hit the age group of 30-44 years with 26.0% and of whom 34/420 (8.1%) were rifampicin resistant. The positivity nding was in line with studies conducted in Gondar (29.8%) [14], different studies in Ethiopia [21][22][23]35], WHO reports 2017 [2] and Agaro Teaching Health Center in southwestern Ethiopia [36].However, contrary ndings with several studies in a different part of Nigeria and Zambia [18,24,33] which had lower prevalence, but higher than a study conducted in eastern Uttar Pradesh (40%) [19].…”
Section: Discussionsupporting
confidence: 83%
“…However, it was lower compared to reports in Jigjiga (65.5%) [17], Kenya (32.25%) [18], in eastern Uttar Pradesh (32.9%) [19] and Congo (79.1%) [47].The main difference in these latter ndings may show our inclusion of all forms of presumptive tuberculosis while other studies included identi ed cases of Mycobacterium tuberculosis. In contrast, our nding was higher when compared with studies conducted in Metema and Armacho (5.7%) [6], Felege Hiwot Referral Hospital, and Debre Tabor Hospital (14.6%) [20], in three referral hospitals and the regional laboratory in Addis Ababa (15.11%) [48], other parts of Ethiopia (4.7%-10.8%) [21][22][23], Nigeria (10.3%) [24] and India (2.31%) [25].The variations might be due to the difference in study design, type and number of participants, and environmental conditions.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…the main difference in these latter findings may show our inclusion of all forms of presumptive tuberculosis while other studies included identified cases of Mycobacterium tuberculosis. In contrast, our finding was higher when compared with studies conducted in Metema and Armacho (5.7%) [6], Felege Hiwot Referral Hospital, and Debre Tabor Hospital (14.6%) [20], in three referral hospitals and the regional laboratory in Addis Ababa (15.11%) [48], other parts of Ethiopia (4.7%-10.8%) [21][22][23], Nigeria (10.3%) [24] and India (2.31%) [25].The variations might be due to the difference in study design, type & number of participants, and environmental conditions.…”
Section: Discussioncontrasting
confidence: 83%
“…The positivity finding was in line with studies conducted in Gonder (29.8%) [14], different studies in Ethiopia [21][22][23]35], WHO reports 2017 [2] & Agaro Teaching Health Center in southwestern Ethiopia [36]. There are however contrary findings with several studies in a different part of Nigeria and Zambia [18,24,33] which had lower prevalence, but higher than a study conducted in eastern Uttar Pradesh (40%) [19].…”
Section: Discussionsupporting
confidence: 81%